THE FINANCIAL SPHERE TRANSFORMATION OF THE RUSSIAN FEDERATION’S REGIONS IN THE CONDITIONS OF INCREASING EXTERNAL THREATS - Ekaterina Aleksandrovna Zakharchuk (Science and Innovation Center Publishing House, 2020)
In recent years, threats to the socio-economic development of both the Russian Federation as a whole and individual regions have been growing to a significant extent. This is primarily reflected in the financial sector, since the policy of sanctions against Russia is primarily based on blocking the possibilities of using various financial instruments abroad. A further increase in threats can lead to various forms of emergencies in the economy and financial sphere. At the same time, the question of the influence of special regimes on the financial sphere of individual regions, which can be heterogeneous depending on the capabilities of the territories, remains poorly understood.